Comment on Gomez et. al. "Response to article by Wasserman et. al. (2018) 'Modelling the sustained use of the 13-valent pneumococcal conjugate vaccine compared to switching to the 10-valent vaccine in Mexico'". Issue 3 (4th March 2019) - Wasserman, Matt; Palacios, Maria Gabriela; Grajales, Ana Gabriela; Wilson, Michele; McDade, Cheryl; Farkouh, Raymond
ABSTRACT: In a recent Letter, Gomez et. al. provided a critique of our original analysis estimating the clinical and economic impact of switching from the 13-valent (PCV13) to the 10-valent (PCV10) pneumococcal conjugate vaccine in Mexico. This comment addresses Gomez et. al.'s comments with additional information and clarifies potential misinterpretations.